2015
DOI: 10.1590/1807-2577.1077
|View full text |Cite
|
Sign up to set email alerts
|

Survival time of direct dental restorations in adults

Abstract: ResumoIntrodução: A cárie dentária é o principal motivo para a instalação e troca de restaurações. A preservação destas em condição clínica satisfatória é um desafio, apesar da evolução dos materiais e técnicas cirúrgico-operatórias. Objetivo: Investigar o tempo de sobrevida e características técnico-operatórias das restaurações dentárias diretas de adultos em Teresina, Piauí. Material e método: A coleta de dados ocorreu de setembro de 2009 a janeiro de 2010, em clínicas de tratamento odontológico sem fins luc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(49 reference statements)
1
0
0
Order By: Relevance
“…In this survey, the results indicated that the participants were more inclined towards teaching that the composite resin should be routinely placed on the premolar site while amalgam restorations should be mostly performed at the molar site. This is in line with previous studies that showed that amalgam has a high survival rate, with the majority of studies reporting more than 85% survival rate in an extensive cavities [46][47][48]. Moreover, composite resin restoration also has a low failure rate, with the majority of studies reporting an annual failure rate of less than 5%, thus making it a desirable material of choice for posterior teeth [1].…”
Section: Discussionsupporting
confidence: 89%
“…In this survey, the results indicated that the participants were more inclined towards teaching that the composite resin should be routinely placed on the premolar site while amalgam restorations should be mostly performed at the molar site. This is in line with previous studies that showed that amalgam has a high survival rate, with the majority of studies reporting more than 85% survival rate in an extensive cavities [46][47][48]. Moreover, composite resin restoration also has a low failure rate, with the majority of studies reporting an annual failure rate of less than 5%, thus making it a desirable material of choice for posterior teeth [1].…”
Section: Discussionsupporting
confidence: 89%